Library Technician course recognition in Australia: The challenges of a distributed national education program - Genoni, Paul; Hallam, G. (International Federation of Library Associations, 2008)
This paper looks at the challenges presented for the Australian Library and Information Association by its role as the professional association responsible for ensuring the quality of Australian library technician graduates. There is a particular focus on the issue of course recognition, where the Association’s role is complicated by the need to work alongside the national quality assurance processes that have established by the relevant technical education authorities. The paper describes the history of course recognition in Australia; examines the relationship between course recognition and other quality measures; and describes the process the Association has recently undertaken in order to ensure appropriate professional scrutiny without unnecessary duplication of effort and expense.